Inner Encapsulating Approach for Moisture‐Stable Perovskite Solar Cells. Issue 9 (20th July 2021) - Kim, Yong Ryun; Kim, Juae; Kim, Heejoo; Yoon, Chang-Jae; Yun, Jun-Tae; Kim, Ju-Hyeon; Gu, Ayeong; Suh, Hongsuk; Lee, Kwanghee
Abstract : The degradation of the perovskite layer in atmospheric air is a critical bottleneck for the commercialization of perovskite solar cells (PSCs). As the moisture and oxygen in air penetrate the charge transport layer/top metal electrode interface, both adjacent layers and perovskite layers decompose in the PSCs. Herein, moisture‐stable inverted PSCs (I‐PSCs) based on methylammonium lead triiodide (MAPbI3 ) by introducing amine‐functionalized small molecules as metal adhesive layers (MALs) between the electron transport layer (ETL) and metal electrode (here, Cu) are demonstrated. A strong coordination bond of CuN forms at the Cu/MAL interface, leading to the layer–layer growth mode for the dense formation of Cu electrodes with a strong adhesion to the ETL. Thus, this modified electrode prevents the ingress of moisture into the I‐PSCs, resulting in outstanding moisture stability; the efficiency of I‐PSCs retains 90% of the initial efficiency after 200 days of exposure to atmospheric air (25 °C, relative humidity [RH] ≈20–40%). Under harsher conditions (e.g., 25 °C/RH65%, 25 °C/RH85% and immersion in water) for a considerable time period, the modified I‐PSCs manifest relatively no degradation compared with the pristine I‐PSCs. It is believed that this breakthrough provides a significant impact on improving the stability of I‐PSCs. Abstract : The moisture instability of perovskite solar cells is addressed using an inner encapsulating technology that uses a metal adhesive layer for the formation of a compact metal electrode, which can effectively stop the penetration of moisture into the adjacent layer and perovskite materials, resulting in a moisture‐resilient perovskite solar cell without additional encapsulation.